THE EFFECT OF ESG AWARENESS AND BRIMO APPLICATION FEATURE INNOVATION ON THE INTEREST IN USING THE BRIMO APPLICATION THROUGH CUSTOMER SATISFACTION - Nurul Islamiah; Jumawan Jasman; Hapid Hapid (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the effect of ESG awareness and innovation in BRImo application features on users’ intention to use the BRImo application through customer satisfaction. The study is motivated by the increasing need for innovative and sustainable digital banking services in response to rapid digital transformation in the banking sector.Methods: This research employs a quantitative method with an explanatory research approach. Data were collected through questionnaires distributed to BRImo application users in Palopo City. A total of 400 respondents were selected using a purposive sampling technique. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 3.0 software.Results: The results indicate that ESG awareness and innovation in BRImo application features have a positive and significant effect on customer satisfaction and users’ intention to use the application. In addition, customer satisfaction is proven to partially mediate the relationship between ESG awareness and feature innovation on the intention to use BRImo.Conclusion and suggestion: The findings confirm that the success of banking digitalization is not only determined by technological innovation but also by the implementation of sustainability values that can enhance customer trust and loyalty. Keywords: BRImo, Customer Satisfaction, Digital Innovation, ESG